Model Pembelajaran Ilmu Ushûl Fiqh di Jurusan Pendidikan Agama Islam (Analisis Penerapan Model Pembelajaran Konvensional dan Pembelajaran Berbasis Masalah) - Sapiudin, Sapiudin; Nata, Abuddin; Syihab, Usman (Ta'dibuna: Jurnal Pendidikan Islam, 2016)
Learning System of Islamic Education (PAI) is still considered as low, including that of Ushûl Fiqh. In Departement of Islamic Education, the subject of Ushûl Fiqh must be taken by all students. However, since the learning system used is still expository approach based on teacher centred approaches which use speech method in explainning the subject. Consequently, the students do not understand the substance of Ushûl Fiqh well. Therefore, the learning system of Ushûl Fiqh can be regarded as ineffective. The focus of this research is to see the efectivity of convensional learning model and a model of learning based on problem. The research is focussed on the purpose, method, subject matter and evaluation of learning Ushûl Fiqh in Departement of Islamic Education with the goal, to find the effective model of learning Ushul fiqh. The result of observation and interview about the use of Ushûl Fiqh learning system held in two departements of Islamic Education (PAI) is that the activity of learning Ushûl Fiqh is far from what is expected. From the aspect of purpose, learning Ushûl Fiqh can only make the student “know”, not “expert”. From that of method, it is only dominated by speech method, and from that of evaluation, it can only measure cognitive ability of the student, but not their affective and psychomotoric. Ushûl Fiqh learning system will be success if the model used challenge student to think constructively and contextually by using participative learning principles in analyzing formulas in the science of Ushûl Fiqh. In addition, the method used is varied and encourages the student to do by him/herself through practice and task method. In term of evaluation system, it is comprehensive, not only to measure cognitive aspect, but also affective and pschycomotoric aspect simultaneously. Keywords: Model Pembelajaran, Ushul Fiqh, Pembelajaran Berbasis Masalah